Pengaruh Tingkat Fertilitas, Kesehatan, dan Tingkat Pengangguran terhadap Pekerja Wanita dalam Perspektif Ekonomi Islam di 5 Kawasan Asean 2018-2022 - Luluk Wachidatu Zahro; Diah Mukminatul Hasyim; Nurhayati Nurhayati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Female workers have a double burden of work and household responsibilities compared to men. Women workers are often underestimated and even socially discriminated against for their household responsibilities, even though household responsibilities lie with both of them. The physical shape, health and fertility level of women in productive age are often vulnerable to problems due to age and even height limits in the application of some employment opportunities so that many women have difficulty finding work that suits their biological factors, especially women of productive age who are partly hindered by being married. and some of them are not allowed to work to look after many children. This research aims to determine the influence of fertility, health and unemployment rates on female workers from an Islamic economic perspective in 5 ASEAN regions 2018-2022. This research uses quantitative methods with panel data regression data analysis, data processing uses Eviews version 12. Secondary data is obtained from the world bank, but data processing uses Eviews. The results of this study show that fertility partially has a negative and significant effect on female workers, health partially has a positive and insignificant effect on female workers, the unemployment rate partially has a positive and insignificant effect on female workers, and simultaneously fertility, health and level Unemployment together has a significant effect on female workers.